Marine bacterioplankton community turnover within seasonally hypoxic waters of a subtropical sound: Devil's Hole, Bermuda. (18th April 2014) - Parsons, Rachel J.; Nelson, Craig E.; Carlson, Craig A.; Denman, Carmen C.; Andersson, Andreas J.; Kledzik, Andrew L.; Vergin, Kevin L.; McNally, Sean P.; Treusch, Alexander H.; Giovannoni, Stephen J.
Summary Understanding bacterioplankton community dynamics in coastal hypoxic environments is relevant to global biogeochemistry because coastal hypoxia is increasing worldwide. The temporal dynamics of bacterioplankton communities were analysed throughout the illuminated water column of Devil's Hole, Bermuda during the 6‐week annual transition from a strongly stratified water column with suboxic and high‐pCO2 bottom waters to a fully mixed and ventilated state during 2008. A suite of culture‐independent methods provided a quantitative spatiotemporal characterization of bacterioplankton community changes, including both direct counts and rRNA gene sequencing. During stratification, the surface waters were dominated by the SAR11 clade of Alphaproteobacteria and the cyanobacterium Synechococcus. In the suboxic bottom waters, cells from the order Chlorobiales prevailed, with gene sequences indicating members of the genera Chlorobium and Prosthecochloris – anoxygenic photoautotrophs that utilize sulfide as a source of electrons for photosynthesis. Transitional zones of hypoxia also exhibited elevated levels of methane‐ and sulfur‐oxidizing bacteria relative to the overlying waters. The abundance of both Thaumarcheota and Euryarcheota were elevated in the suboxic bottom waters (> 109 cells l−1). Following convective mixing, the entire water column returned to a community typical of oxygenated waters, with Euryarcheota only averaging 5% of cells, and Chlorobiales and Thaumarcheota absent.